INVESTIGATING TEACHING STRATEGIES USED BY ENGLISH TEACHERS IN TEACHING ENGLISH AT SMK TI BALI GLOBAL SINGARAJA - ., KADEK MAYA CYNTIA DEWI; ., PROF. DR. I KETUT SEKEN, M.A.; ., DR. LUH PUTU ARTINI, M.A. (Jurnal Pendidikan Bahasa Inggris Indonesia, 2015)
This study was carried out to describe teaching strategies used by teachers in teaching English and to know how students perceive the strategies used by the teachers in teaching English at SMK TI Bali Global Singaraja. This study was designed as a qualitative study by applying seven Killen’s teaching strategies namely Direct Instruction, Discussion, Group Work, Co-operative Learning, Problem Solving, Performance Activities and Student Research. The data collection was done through observation, questionnaire, and interview. The results showed that English teachers at SMK TI Bali Global Singaraja used five of seven Killen’s teaching strategies in teaching English to their students namely direct instruction, discussion, group work, Co-operative Learning and performance activity. Students had different perception about the strategies that they like when the teacher taught English. Some others claim that they did not like group work and discussion because they can share their opinion and experiences each other, some students also didn’t like group work because they perceive that only clever students did the exercises without discussing it with the other members of the group. This study has an implication to the importance of understanding types of strategies and when and how to implement to improve the quality of instructional process in the classroom.keyword : strategy, teaching English, vocational school.